What Is Informal Social Control?: a Concept Consensus Review of Recent Criminological Literature - Linning, Shannon J. (Canadian journal of criminology and criminal justice, 2024)
Is there consensus among criminologists about the meaning of informal social control? Some prominent criminologists say no. We conduct a concept consensus review of all articles using the term in the top 10 journals in criminology from 2010 to 2020 to test their dissensus assertion. We found 597 articles that mention informal social control. Of the 228 articles where the term was important to the study, only 41 attempt to define the concept. We assessed each conceptual definition using four definitional elements: subject, action, object, and reason. One or more elements were missing from most conceptual definitions. Combining the mode of the most specified elements, informal social control may mean "residents intervening with youth/children to reduce crime." But dissensus is more common than consensus; authors differ on who applied controls, what those controls were, who was controlled, or the reasons for the control. This raises questions about how to proceed with the study of informal social control.